SUSTAINABLE PRODUCTION FLEXIBLE IMPROVEMENT BY INTERNAL ACTIVITIES TIME REDUCTION IN MANUFACTURING INDUSTRY - A.H. Abdul Rasib , R. Mahamad Noor, M.N. Ahmad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Nowadays, the manufacturing sectors are in the process of increasing their performance to extend productivity because there are so many challenges from competitors in the same sectors, especially in the food industry. The purpose of this study is to propose improvements to increase sustainability of food operation flexibility through secondary data collection, Cause and effect diagram analysis, and the Why-why Analysis tool. Besides, improving the understanding of Single Minute Exchange of Dies (SMED) factors in the production line can be applied by changing the internal activities to become external activities. This study is useful for manufacturing managers and companies who are willing to increase their flexibility and at the same time reduce the changeover time within their available resources without compromising the machine efficiency and cost. In conclusion, this study has provided a better understanding of reducing internal activities that cause high changeover time.